A sulfur / flower-like Fe(OH) 3 Lithium-sulfur battery positive electrode material and preparation method thereof

By using sulfur/flower-like Fe(OH)3 composite material as the positive electrode material of lithium sulfur batteries, the problems of shuttle effect, volume expansion and low battery capacity of lithium sulfur batteries in practical applications are solved, and high specific capacity and excellent electrochemical performance are achieved.

CN116111073BActive Publication Date: 2025-03-18GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310271313.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-20
Publication Date
2025-03-18
Estimated Expiration
2043-03-20

AI Technical Summary

Technical Problem

In practical applications, lithium-sulfur batteries have problems such as shuttle effect, structural damage caused by volume expansion and low battery capacity.

Method used

Sulfur/flower-like Fe(OH)3 is used as the positive electrode material of the lithium sulfur battery. By grinding and mixing the flower-like Fe(OH)3 with elemental sulfur, and heating treatment is performed in a tube furnace to form a composite material.

Benefits of technology

The initial discharge specific capacity of the material at a current density of 0.1C reaches 1122mAh/g, showing excellent electrochemical properties, which can effectively alleviate the problems of shuttle effect and volume expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116111073B_ABST
    Figure CN116111073B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-sulfur batteries, specifically a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material and a preparation method thereof, comprising: 1) dissolving iron salt and sodium carbonate in anhydrous ethanol and ultrapure water respectively, ultrasonically dissolving, obtaining an iron salt-anhydrous ethanol solution and a sodium carbonate aqueous solution; injecting the configured sodium carbonate aqueous solution into the iron salt-anhydrous ethanol solution with a syringe, and standing at room temperature for reaction; after the reaction is completed, a precipitate is obtained, the precipitate is centrifugally cleaned, and dried to obtain a flower-shaped Fe(OH)3; 2) grinding and mixing the obtained flower-shaped Fe(OH)3 with elemental sulfur, mixing evenly and placing in a tubular furnace for heat treatment, and obtaining a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material after the reaction is completed. The positive electrode material prepared by the present invention has good electrochemical properties, and the initial discharge specific capacity of the prepared electrode material at a current density of 0.1C is 1122mAh / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium-sulfur batteries, and in particular to a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material and a preparation method thereof. Background Art

[0002] The current energy shortage and environmental pollution problems have greatly stimulated the research and development of efficient electrochemical energy storage devices. Lithium-sulfur batteries have a high theoretical specific capacity of 1675 mAhg -1 And theoretical energy density 2567Whkg -1 In addition, elemental sulfur has the characteristics of low price, non-toxicity, and environmental friendliness. Therefore, lithium-sulfur batteries are considered to be one of the most promising new generation energy storage devices.

[0003] However, there are still many problems that hinder the development of lithium-sulfur batteries in practical applications. For example: (1) The shuttle effect caused by the dissolution and diffusion of polysulfides. (2) The elemental sulfur (2.03 g cm -3 ) and LiS2 (1.67 g·cm -3 ) The volume expansion caused by the density difference leads to material structure damage. (3) Low battery capacity caused by the insulation of elemental sulfur, polysulfide and sulfide.

[0004] The study found that the cathode material prepared by using transition metal hydroxide as sulfur carrier showed efficient catalytic performance and excellent stability in alkaline electrolyte. Fe(OH)3 is a low-cost and easily available transition metal compound with abundant hydrophilic hydroxyl groups (-OH) on its surface. These hydroxyl groups have a strong chemical adsorption effect on polysulfides. Therefore, the characteristics of transition metal hydroxides are used to prepare materials with high specific surface area and a large number of pore structures, which has a strong driving effect on the development of cathode materials for lithium-sulfur batteries. Summary of the invention

[0005] In view of the above problems, the present invention provides a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material and a preparation method thereof. The sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material has good electrochemical properties. The prepared electrode material has an initial discharge specific capacity of 1122 mAh / g at a current density of 0.1C.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material comprises the following steps:

[0008] (1) Preparation of flower-shaped Fe(OH)3: Dissolve iron salt and sodium carbonate in anhydrous ethanol and ultrapure water respectively, and sonicate for 10-20 minutes. After complete dissolution, obtain an iron salt-anhydrous ethanol solution and a sodium carbonate aqueous solution; quickly inject the prepared sodium carbonate aqueous solution into the iron salt-anhydrous ethanol solution with a syringe, and let it stand at room temperature for 20-40 minutes to react; after the reaction is completed, obtain a precipitate, centrifuge and wash the precipitate, and dry it to obtain a flower-shaped Fe(OH)3;

[0009] (2) Preparation of positive electrode material for lithium-sulfur battery: Grind and mix the flower-shaped Fe(OH)3 obtained in step (1) with elemental sulfur. After mixing evenly, place the mixture in a tubular furnace for heating treatment. After the reaction is completed and the temperature is cooled to room temperature, take out the sample to obtain sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material.

[0010] In the present invention, further, the iron salt is ferric chloride or ferric sulfate.

[0011] In the present invention, further, the volume ratio of the sodium carbonate aqueous solution to the iron salt-anhydrous ethanol solution in step (1) is 1:140-160.

[0012] In the present invention, further, the amount of the iron salt in step (1) is 0.2-0.4 g, and the amount of the anhydrous ethanol is 280-480 ml.

[0013] In the present invention, further, the amount of sodium carbonate used in step (1) is 0.3-0.5 g, and the amount of ultrapure water used is 2-4 ml.

[0014] In the present invention, further, the needle tube is a 1 ml syringe, and the needle diameter of the syringe is 0.7 mm.

[0015] In the present invention, further, the centrifugal speed of the centrifugal washing in step (1) is 2000r / min-4000r / min, and the centrifugal time is 4-6min; the centrifugal washing step of the precipitate is specifically: first, the precipitate is washed 3-5 times with anhydrous ethanol, and then the precipitate is washed 3-5 times with deionized water; the drying temperature of the drying is 50-70°C, and the time is 10-15h.

[0016] In the present invention, further, the mass ratio of the flower-shaped Fe(OH)3 and elemental sulfur in step (2) is 2:3.

[0017] In the present invention, further, the inert gas in step (2) is nitrogen or argon; the temperature of the heating treatment is 130-150°C, the heating time is 12-18h, and the heating rate is 2-3°C / min.

[0018] The present invention also provides a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material obtained by the above-mentioned preparation method.

[0019] By adopting the above technical solution, the beneficial effects of the present invention are:

[0020] In the present invention, the prepared sodium carbonate aqueous solution is quickly injected into the iron salt-anhydrous ethanol solution by a syringe, and the reaction is allowed to stand at room temperature for 20-40 minutes, etc., so that the synthesis method of the flower-shaped Fe (OH) 3 of the present invention is green, environmentally friendly, convenient and efficient, so that the prepared sulfur / flower-shaped Fe (OH) 3 composite material can not only utilize the rich pore structure of the carrier flower-shaped Fe (OH) 3 to adsorb elemental sulfur and polysulfide, but also utilize its own characteristics of being rich in a large number of hydroxyls to capture polysulfide, while alleviating the generation of the shuttle effect in terms of physical restriction and chemical adsorption. In addition, the unique structure of flower-shaped Fe (OH) 3 provides sufficient space for the volume expansion generated by elemental sulfur during battery charging and discharging. Therefore, the present invention uses flower-shaped Fe (OH) 3 as a carrier of sulfur, giving full play to its advantages, so that the prepared composite material has excellent electrochemical properties.

[0021] Electrochemical tests show that the sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material prepared by the present invention has good electrochemical properties, and the initial discharge specific capacity of the prepared electrode material at a current density of 0.1C is 1122mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the flower-shaped Fe(OH)3 material prepared in Example 1 of the present invention;

[0023] Figure 2 This is the XRD pattern of the composite material prepared in Example 1 of the present invention;

[0024] Figure 3 This is a SEM image of the flower-shaped Fe(OH)3 material prepared in Example 2 of the present invention;

[0025] Figure 4 This is a comparison chart of the electrochemical cycle performance of the positive electrode materials prepared in Example 1 of the present invention and Comparative Example 1;

[0026] Figure 5 This is a comparison chart of the electrochemical rate performance of the positive electrode materials prepared in Example 1 of the present invention and Comparative Example 1;

[0027] Figure 6 This is a SEM image of the non-flower-shaped Fe(OH)3 material prepared in Comparative Example 3 of the present invention;

[0028] Figure 7This is a comparison chart of the electrochemical cycle performance of the positive electrode materials prepared by Example 1 of the present invention and Comparative Examples 2 and 3. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] This embodiment provides a method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material, comprising the following steps:

[0032] (1) Preparation of flower-shaped Fe(OH)3: Dissolve ferric chloride and sodium carbonate in anhydrous ethanol and ultrapure water respectively, sonicate for 20 minutes, and obtain a pale yellow ferric chloride anhydrous ethanol solution and a transparent sodium carbonate aqueous solution after complete dissolution. Then mix the transparent sodium carbonate aqueous solution and the ferric chloride anhydrous ethanol solution in a volume ratio of 1:150. Specifically, dissolve 0.34g FeCl3 and 0.3g NaCO3 in 300ml anhydrous ethanol and 2ml ultrapure water respectively, sonicate for 20 minutes, and obtain the configured pale yellow ferric chloride anhydrous ethanol solution and transparent sodium carbonate aqueous solution after complete dissolution. Quickly inject the configured NaCO3 aqueous solution into the FeCl3 anhydrous ethanol solution using a 1ml syringe (syringe) (i.e., quickly inject twice using a 1ml syringe), and let it stand for reaction at room temperature for 30 minutes. After the standing reaction is completed, a precipitate is obtained, which is centrifuged and washed, and dried to obtain a flower-shaped Fe(OH)3 material. The centrifugal washing step includes firstly washing the precipitate three times by centrifugation using anhydrous ethanol, and then washing the precipitate three times by centrifugation using deionized water; the centrifugal speed during the centrifugation is 3000 r / min, and the time is 5 min.

[0033] (2) Preparation of positive electrode material for lithium-sulfur battery: 0.2 g of the flower-shaped Fe(OH)3 obtained in step (1) and 0.3 g of elemental sulfur are ground and mixed, and poured into a crucible after being evenly mixed, and the crucible is placed in a tube furnace for heating treatment. After the reaction is completed and the temperature is cooled to room temperature, the sample is taken out to obtain sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material. The temperature during the heating treatment is 150°C, the heating time is 18h, and the heating rate is 3°C / min.

[0034] (3) Preparation of battery: 0.21 g of the electrode material prepared in step (2), 0.06 g of acetylene black and 0.03 g of PVDF (polyvinylidene fluoride) were mixed, and solvent NMP (N-methyl-2-pyrrolidone) was added. The mixture was stirred until it became a paste, and then evenly coated on a copper foil with a thickness of 10 μm. The copper foil was then placed in a forced air drying oven and dried at 60°C for 6 h. The copper foil was then transferred to a vacuum drying oven at 70°C and dried in vacuum for 24 h. The copper foil was punched into 16 mm round pieces using a manual punching machine. shaped electrode piece, with the circular electrode piece as the positive electrode, the lithium sheet as the negative electrode, the microporous polypropylene membrane as the separator, 1 mol / L LiPF6 / EC (ethylene carbonate) + DMC (dimethyl carbonate) + DEC (diethyl carbonate) as the electrolyte (LiPF6 in the electrolyte is the solute, and the solvent is DEC, DMC and EC with a volume ratio of 1:1:1), a button battery with a simulated model CR2025 is assembled in an argon-filled glove box, and after sealing, it is placed in a ventilated place for 12 hours.

[0035] During the electrochemical performance test, the battery test voltage range is 1.5-2.8V, and the test current is determined according to the mass of the active substance on the electrode material.

[0036] The positive electrode material prepared in this example is recorded as: 2-3-30.

[0037] Figure 1 , Figure 2 The following are the SEM image of the flower-shaped Fe(OH)3 obtained in Example 1 and the XRD image of the composite material. Figure 1 It can be seen that the surface of the material is evenly dispersed with trumpet-shaped holes. Such holes can not only facilitate the storage of sulfur but also alleviate the volume effect. In addition, they can also play a physical adsorption role on polysulfides.

[0038] from Figure 2 It can be seen that the Fe(OH)3 curve does not have an obvious crystal peak, indicating that the synthesized material is amorphous, which is consistent with the conclusion of Fe(OH)3. In the curve of sulfur / flower-like Fe(OH)3 composite material, a diffraction peak corresponding to elemental sulfur appears, indicating that elemental sulfur is successfully loaded on the flower-like Fe(OH)3 material.

[0039] Example 2

[0040] This embodiment provides a method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material. The method is basically the same as that in Example 1, except that: in this embodiment, the static reaction time of step (1) is 20 minutes.

[0041] The SEM images of the flower-like Fe(OH)3 material prepared in this example are as follows: Figure 3 As shown, it can be seen that trumpet-shaped holes are evenly distributed on the surface of the material.

[0042] Example 3

[0043] This embodiment provides a method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material, which is basically the same as that in Example 1, except that: in this embodiment, the masses of FeCl3 and NaCO3 in step (1) are 0.39 g and 0.32 g, respectively.

[0044] Example 4

[0045] This embodiment provides a method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material. The method is basically the same as that in Example 1, except that: in this embodiment, the anhydrous ethanol in step (1) is 480 ml and the ultrapure water is 3 ml.

[0046] Example 5

[0047] This embodiment provides a method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material, which is basically the same as that in Example 1, except that: in this embodiment, the sulfurization temperature of step (2) is 140°C and the sulfurization time is 16 hours.

[0048] Comparative Example 1

[0049] This comparative example provides a method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material. The method is basically the same as Example 1, with the only difference being that in step (2), the masses of the flower-shaped Fe(OH)3 and elemental sulfur in this example are 0.15 g and 0.3 g, respectively, that is, the mass ratio of the flower-shaped Fe(OH)3 to the elemental sulfur is 1:2.

[0050] The positive electrode material obtained in this comparative example is recorded as: 1-2-30.

[0051] In order to verify the electrochemical performance of the composite positive electrode material prepared by the present invention, the applicant also conducted cycle performance tests and rate performance tests on the positive electrode materials prepared by Example 1 and Comparative Example 1. The testing conditions of the positive electrode material obtained by Comparative Example 1 were the same as those of Example 1.

[0052] like Figure 4 , Figure 5 As shown, electrochemical tests show that the long cycle performance and rate performance of the obtained positive electrode material are related to the mass ratio of Fe(OH)3 material and elemental sulfur. When the mass ratio of Fe(OH)3 material and elemental sulfur is 2:3, the obtained positive electrode material has the best long cycle performance and rate performance. At 0.1C, its initial discharge specific capacity is 1122mAh / g.

[0053] Comparative Example 2

[0054] This comparative example provides a method for preparing a sulfur / non-flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material, which is basically the same as Example 1, except that in this comparative example, the NaCO3 aqueous solution is added to the FeCl3 anhydrous ethanol solution in step (1) by dropper addition.

[0055] The positive electrode material prepared in this comparative example is recorded as: non-flower-shaped 1

[0056] Comparative Example 3

[0057] This comparative example provides a method for preparing a sulfur / non-flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material, which is basically the same as Example 1, except that in this comparative example, in step (1), the prepared NaCO3 aqueous solution is quickly injected into the FeCl3 anhydrous ethanol solution using a 1 ml syringe, and after a mixed solution is formed, the mixed solution is stirred evenly, that is, stirred for 30 minutes, and then allowed to react at room temperature for 30 minutes.

[0058] The positive electrode material prepared in this comparative example is recorded as: non-flower-shaped 2.

[0059] The SEM of the non-flower-like Fe(OH)3 material prepared in this comparative example is shown in Figure 6 As shown, it can be seen that there is no trumpet-shaped hole structure on the surface of the material.

[0060] In the above embodiments and comparative examples, the preparation of the battery and the testing of the electrochemical performance are the same as those in Example 1.

[0061] In addition, in order to further verify the electrochemical performance of the sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material prepared by the present invention, the applicant also conducted a cycle performance test on the positive electrode materials prepared by Example 1 and Comparative Example 2 and Comparative Example 3 and made a comparison. The results are as follows: Figure 7 As shown, by comparing the data in the figure, it is found that the discharge specific capacity and cycle performance of the positive electrode material (2-3-30) prepared in Example 1 are significantly better than the discharge specific capacity and cycle performance of the positive electrode materials (non-flower-shaped) prepared in Comparative Examples 2 and 3, indicating that the embodiment of the invention quickly injects the prepared NaCO3 aqueous solution into the FeCl3 anhydrous ethanol solution with a 1 ml syringe and directly allows the reaction to stand after injection instead of stirring first and then allowing it to stand, which is of great significance to the formation of the flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material and the electrochemical properties of the positive electrode material.

[0062] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.

Claims

1. A method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material, characterized in that: The steps include: (1) Preparation of flower-shaped Fe(OH)3: Dissolve iron salt and sodium carbonate in anhydrous ethanol and ultrapure water respectively, and sonicate for 10-20 minutes. After complete dissolution, obtain an iron salt-anhydrous ethanol solution and a sodium carbonate aqueous solution; quickly inject the prepared sodium carbonate aqueous solution into the iron salt-anhydrous ethanol solution with a syringe, and let it stand at room temperature for 20-40 minutes to react; after the reaction is completed, obtain a precipitate, centrifuge and wash the precipitate, and dry it to obtain a flower-shaped Fe(OH)3; (2) Preparation of positive electrode material for lithium-sulfur battery: Grind and mix the flower-shaped Fe(OH)3 obtained in step (1) with elemental sulfur. After mixing evenly, place the mixture in a tubular furnace for heating treatment. After the reaction is completed and the temperature is cooled to room temperature, take out the sample to obtain sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material.

2. The method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material according to claim 1, characterized in that: The iron salt is ferric chloride or ferric sulfate.

3. The method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material according to claim 1, characterized in that: The volume ratio of the sodium carbonate aqueous solution to the iron salt-anhydrous ethanol solution in step (1) is 1:140-160.

4. The method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material according to claim 3, characterized in that: In step (1), the amount of the iron salt is 0.2-0.4 g, and the amount of the anhydrous ethanol is 280-480 ml.

5. The method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material according to claim 3, characterized in that: The amount of sodium carbonate used in step (1) is 0.3-0.5 g, and the amount of ultrapure water used is 2-4 ml.

6. The method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material according to claim 1, characterized in that: The needle tube is a 1 ml syringe, and the needle diameter of the syringe is 0.7 mm.

7. The method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material according to claim 1, characterized in that: The centrifugal speed of the centrifugal washing in step (1) is 2000r / min-4000r / min, and the centrifugal time is 4-6min; the steps of the centrifugal washing are specifically as follows: first, the precipitate is washed 3-5 times with anhydrous ethanol, and then, the precipitate is washed 3-5 times with deionized water.

8. The method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material according to claim 1, characterized in that: The mass ratio of the flower-shaped Fe(OH)3 and elemental sulfur in step (2) is 2:

3.

9. The method for preparing a sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material according to claim 1, characterized in that: The temperature of the heating treatment in step (2) is 130-150°C, the heating time is 12-18h, and the heating rate is 2-3°C / min.

10. A sulfur / flower-shaped Fe(OH)3 lithium-sulfur battery positive electrode material prepared according to the method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Core molecule-based molecular assembled superstructure material, preparation method and application

    CN107017389A

  • Method for preparing iron hydroxide (FEOOH), and lithium-sulfur battery cathode comprising iron hydroxide

    CN109792039A